2018
DOI: 10.1136/bjophthalmol-2017-311766
|View full text |Cite
|
Sign up to set email alerts
|

Microinterventional endocapsular nucleus disassembly: novel technique and results of first-in-human randomised controlled study

Abstract: AimTo assess the safety and efficacy of microinterventional endocapsular nuclear fragmentation in moderate to severe cataracts.MethodsThis was a prospective single-masked multisurgeon interventional randomised controlled trial (ClinicalTrials.gov NCT02843594) where 101 eyes of 101 subjects with grade 3‒4+ nuclear cataracts were randomised to torsional phacoemulsification alone (controls) or torsional phacoemulsification with adjunctive endocapsular nuclear fragmentation using a manual microinterventional nitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The advantages were effective reduction of ultrasound energy, endothelial damage, and eye stress. Ianchulev et al (20) also reported lower rate of endothelial cell loss caused by combined nucleus fragmentation than by phacoemulsification alone. However, the present study lacks data on endothelial cell detection as this is a retrospective analysis, so further prospective studies or randomized controlled studies to supplement our results are required.…”
Section: Discussionmentioning
confidence: 96%
“…The advantages were effective reduction of ultrasound energy, endothelial damage, and eye stress. Ianchulev et al (20) also reported lower rate of endothelial cell loss caused by combined nucleus fragmentation than by phacoemulsification alone. However, the present study lacks data on endothelial cell detection as this is a retrospective analysis, so further prospective studies or randomized controlled studies to supplement our results are required.…”
Section: Discussionmentioning
confidence: 96%
“…The prechopping techniques including the miLOOP (Carl Zeiss Meditec, Dublin, USA) technique fragment the hard nucleus into smaller fragments, thereby reducing the phaco time and energy used. 23 However, there are challenges involved in fragmenting the brunescent nucleus into six or eight smaller fragments. Furthermore, the movement of large nuclear fragments in the anterior chamber to cause mechanical trauma to the corneal endothelium still continues.…”
Section: Discussionmentioning
confidence: 99%
“… 15 For surgeons who prefer femtosecond laser–assisted cataract surgery, strategies to improve workflow and reduce time such as moving the laser to the operating room or alternatives to laser-assisted capsulotomy such as zepto and miLoop for dense lenses might be of consideration. 16 19 Furthermore, same-day sequential cataract surgery might be considered for patients needing bilateral surgery owing to considerations of anisometropia and intended monovision. 20 It might be possible to covert some postoperative visits to telemedicine or to defer them altogether without compromising patient safety.…”
Section: Discussionmentioning
confidence: 99%